Impact of climate change on the productivity and adaptation of Ethiopia's Bonga and Menz sheep breeds - Tesema, Zeleke; Getachew, Tesfaye; Belay, Berhanu; Amha, Yosef; Rekik, Mourad; Rischkowsky, Barbara A.; Besufkad, Shanbel; Abate, Zelalem; Bekele, Tamrat; Demissie, Teferi; Solomon, Dawit; Haile, Aynalem (Elsevier, 2025)
This study aimed to derive novel phenotypes of sheep resilience and response to climate change, to estimate genetic parameters for novel phenotypes, and to evaluate the genetic correlation of resilience indicator traits with economically important traits. This study used the 14 years (2009–2022) of productive, reproductive, pedigree, and climate data to derive resilience and stability phenotypes using a random regression model fitting to the reaction norm function and genetic parameter estimates were estimated from a linear mixed model. The changes in productive and reproductive performance of both sheep breeds in response to environmental descriptors ((temperature-humidity index (THI) and rainfall (RF)) were found to be minimal and not significantly (P > 0.05) different from zero, suggesting that most of these traits showed stable performance independent of THI and RF. The direct heritability (h2) estimate (0.101–0.163) for the resilience of Bonga sheep in terms of weight gain, Kleiber ratio (KR), total lamb birth weight, and annual reproduction rate (ARR) indicated the presence of substantial genetic variance. Nevertheless, the h2 for resilience and stability phenotypes of Bonga sheep in terms of other reproductive traits were found to be low (0.0001 – 0.098). The highest h2 for resilience of Menz sheep was observed for total lamb weaning weight (0.416), followed by body weight (0.145), KR (0.114), and ARR (0.110). The genetic progress of THI-based resilience was favorable for most of the traits of Bonga sheep. The genetic trend for rainfall-based resilience for most productive and reproductive traits of Menz sheep was genetically decreasing slightly. In conclusion, the influence of heat stress and rainfall on the performance of both sheep breeds is minimal. But different lambs and ewes react differently to a changing climate, and there is some level of genetic contribution to the variability of reaction for some traits. This suggests the possibility of improving the resilience of sheep to weather variation through within-breed selection to sustain these sheep breeds' optimal production and reproduction performances in changing climate conditions, although the influence is minimal. Besides, the contribution of the environment to phenotypic variation of resilience and stability phenotypes was high for most traits, which calls for management intervention to enhance sheep resilience to climate change.